Developing the Construct of Speed Ceteris Paribus - Lee, Minjae (Academy of Management, 2023)
Firm speed has long been a construct of interest among managers and researchers. Despite its importance, making a ceteris paribus comparison of speed can be challenging. In the current paper, we suggest an alternative to the conventional way of capturing the speed ceteris paribus. First, we illustrate the concept of faster speed in strategic management research. Second, we use numerical simulation data to illustrate the challenges of the conventional methodology, known as the nonlinear transformation of variables. We show that this method is difficult to apply and may produce an inaccurate measurement of the concept unless the exact functional form is chosen. Third, we suggest an alternative methodology, known as data envelopment analysis. This accounts for the challenges of the conventional methodology when we do not know the accurate functional form for nonlinear transformation, while performing as well as the best of the conventional approach. Finally, by using actual firm data, we show that our suggested methodology can be an effective alternative to the conventional approach of capturing a firm’s speed.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Research Methods; dept.mgt